Mini Review: Potensi Ekstrak Daun Salam (Syzygium polyanthum (Wight) Walp) sebagai Antibakteri - Pramesti , Luh Ratih Widhia; Yuda, Putu Era Sandhi Kusuma; Anita Dewi, Ni Luh Kade Arman; Cahyaningsih, Erna; Sasadara, Maria Malida Vernandes; Widyani Nayaka , Ni Made Dwi Mara (Usadha, 2024)
Infectious diseases by bacteria are one of the problems in the world of health. The therapy that can be given to people with bacterial infections is antibiotics. However, the increasing incidence of antibiotic resistance and bacterial infections requires other antibiotic alternatives such as those sourced from natural materials. Bay leaf (Syzygium polyanthum (Wight) Walp) included in the Myrtaceae family is one of the plants that is widely known among Indonesian people which empirically has properties in curing various diseases. Bay leaves are known to contain secondary metabolite compounds such as flavonoids, tannins, alkaloids, saponins, triterpenoids, steroids, eugenol, and essential oils that function as antibacterials. This literature review aims to discuss the antibacterial activity of bay leaves against gram-positive and gram-negative bacteria as well as the components of active compounds in bay leaves and their mechanism as antibacterials. The method used in the preparation of this review article is the literature study method. This research uses secondary data taken from the results of other researchers' research in the form of scientific articles that have been published in national and international scientific journals with a year limit from 2014 to 2023. Based on the literature study that has been done, it is known that bay leaves have potential as antibacterials against both gram-positive and gram-negative bacteria. The antibacterial activity is known to be related to the content of active compounds such as flavonoids, tannins, alkaloids, saponins, triterpenoids, steroids, phenols, and essential oils.